Analisis Penerapan PSAK 109 Tentang Pelaporan Keuangan Akuntansi Zakat, Infak/Sedekah pada BAZNAS Kabupaten Tegal - Gita Lindri Astuti; Siti Afidatul Khotijah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to see how the application of financial reports at the National Amil Zakat Agency (BAZNAS) of Tegal Regency is in accordance with what is stated in the Statement of Financial Accounting Standards (PSAK) Number 109. The method used in this study is a qualitative descriptive method. The data used are primary data and secondary data. Data were collected by interview and documentation study. The results of this study indicate that the BAZNAS of Tegal Regency has prepared financial reports in accordance with the PSAK No. format. 109 concerning ZIS Accounting, but the indicators for the recognition and measurement of BAZNAS in Tegal Regency have not fully implemented, while the indicators for distribution, presentation and disclosure of BAZNAS in Tegal Regency are in accordance with PSAK No. 109 concerning Accounting for Zakat, Infak/Alms